Environmental Response to the Use of Sewage Sludge on European Mediterranean Degraded Soils - Almendro-Candel, María Belén; Lucas, Ignacio Gómez; Navarro-Pedreño, Jose; Pérez-Gimeno, Ana; Rodríguez-Espinosa, María Teresa; Jordán, Manuel M. (European Journal of Applied Sciences, 2025)
Soils in the Mediterranean region have a low resilience to disturbances and are now extensively degraded both physically and bio-chemically. Inappropriate agricultural practices, exacerbated by other natural and human induced perturbations such as increased drought and forest fire occurrence have caused soil impoverishment and the subsequent abandonment of agricultural land in many regions. One of the most promising approaches to soil rehabilitation on such land is the application of organic wastes. Organic refuses, such as sewage sludge, are commonly used on agricultural land, but are increasingly considered for the reclamation of degraded land and mine deposits. The positive effect of such organic matter, nutrient and microorganism additions are now widely recognised. Very little, however, is known about the detrimental effects of such treatments. The impacts of phytotoxins, heavy metals, salts (especially sodium) and hydrocarbons added via organic wastes are not well enough understood to be thoroughly considered before application. Potential detrimental impacts include accumulation of metals, phosphorus, nitrogen, and resilient aliphatic hydrocarbons, leading to toxicity, nitrate influxes to the groundwater and changes in soil wetting properties.